Ökonomik: Eine Einführung - Homann, Karl (Mohr Siebeck, 2005)
Modern society is »a cooperative venture for mutual advantage« (J. Rawls). This book presents and exemplifies the economic method of analyzing institutional incentives in order to improve our understanding and support of this joint venture to realize gains from trade.
PublicationDate: 20220620